Endometriosis - Kennedy, S; Koninckx, P (2012)
Endometriosis is a complex condition to treat because of uncertainties regarding its aetiology, the variety of its clinical presentation, the absence of a non-invasive diagnostic marker, its impact on quality of life and productivity, and the limited number of treatment options available. There is an absence of high-quality evidence from large randomized controlled trials to guide therapeutic decision-making, which means that health professionals often have to rely upon clinical experience alone. The ultimate aim is to provide care that relieves pain and distress, so as to improve quality of life; however, this is often a difficult challenge. © 2012 John Wiley and Sons, Ltd..